Molecular prospecting for drugs from the sea. - Gayler, K. (IEEE Engineering in medicine and biology magazine)
This study aims to seek new drugs from the marine environment, with a particular focus on venomous animals, in particular the marine cone snail, Conus, a genus of predatory animal with a highly evolved venom and delivery apparatus. These remarkable creatures provide an example of the rich diversity of therapeutic molecules still to be discovered in marine species. In this article, a description of the value of these animals for medical research and the methods used to realize the therapeutic potential of their venom are presented. The study showed that DNA- or gene-based mining can, when coupled with sensitive bioassays, be an environmentally friendly method for discovering novel therapeutic peptides from marine sources. Simple peptide synthesis combined with a sensitive bioassay is the primary screen. This detects those peptides that form a functional 3-D structure spontaneously under the conditions of primary amino acid chain synthesis and oxidation. The screening process therefore selects lead compounds that are simple to manufacture. Spontaneity of folding may also indicate greater stability of the structure under physiological conditions, and the selection procedure, therefore, may pick those peptides with greater inherent stability in vivo, a further bonus that may be related to the success of delivery and survival of the lead compounds when used therapeutically.